Perlindungan Hukum bagi Pemberi Pijaman (Lender) dalam Penyelenggaraan Financial Technology - Adam Jamaluddin (MLJ Merdeka Law Journal, 2021)
In the implementation of fintech lending services, it cannot be denied that there is a possibility of default by one of the parties. In particular, the lender has a greater risk, namely the risk of default due to the failure of the loan recipient to perform his / her performance. Therefore, legal protection is needed for lenders to create a sense of security and create legal certainty. The issues discussed in this study are how the legal protection for lenders (lenders) in the implementation of Financial Technology when there is a default and how to resolve disputes in the implementation of Financial Technology for lenders (lenders). The results of this study are that one of the legal protections for lenders is also regulated in Article 29 of the Financial Services Authority Regulation Number 77 / POJK.01 / 2016 concerning Information Technology-Based Lending and Borrowing Services, including the Principle of Transparency, fair treatment, reliability, confidentiality, and data security and user dispute resolution in a simple, fast and affordable manner and the Operator is obliged to provide compensation to the party that has been injured due to the Operator's mistake or negligence.DOI: https://doi.org/10.26905/mlj.v2i1.6255